Modern Threats and Environmental Problems in the Context of Economic Globalization - I. N. Ismanov (Researchparks Publishing, 2022)
In this article, environmental threats are one of the problems that require attention in the world in the context of globalization. Environmental threats have not bypassed Uzbekistan today. Aspects related to finding the best way to prevent environmental threats by switching to a green economy in the country are highlighted.